Improving Digital Governance through Electronic Traffic Law Enforcement in Indonesia - Rusliadi Rusliadi; Dian Lestari; Ulfah Oktarida Sihaloho; Dian Permata Puspita (Jurnal Pemerintahan dan Politik Lokal, 2026)
This study aims to analyze the implementation of the Electronic Traffic Law Enforcement (ETLE) policy in Makassar City from the perspective of digital transformation in public service delivery. The research employs a qualitative approach, with data collected through observation, in-depth interviews, and documentation. Thematic analysis is applied, supported by XMind to systematically map relationships among key concepts, actors, and policy implementation dynamics. The study adopts a mixed theoretical framework, integrating policy implementation theory, innovation diffusion, technology acceptance, and an ideal policy perspective emphasizing clarity of policy objectives, availability of resources, compliance of target groups, and support from the socio-political environment. The findings indicate that ETLE implementation in Makassar reflects a significant shift toward digital governance in traffic law enforcement, contributing to enhanced transparency, accountability, and service effectiveness. Institutional integration among the police, local government, judiciary, and banking sector demonstrates a collaborative governance model that strengthens policy execution. Nevertheless, several challenges persist, including uneven public understanding of ETLE procedures, limited digital literacy, and declining inter-agency coordination, particularly in data integration and administrative processes. This study concludes that the effectiveness of ETLE implementation is not solely dependent on technological and regulatory readiness, but also on the clarity of policy goals, adequacy of resources, public compliance, and institutional and social support. Therefore, improving inclusive public communication strategies, strengthening inter-agency system integration, and developing adaptive policy approaches are essential. This research contributes to public administration literature by offering a visual and integrative analytical perspective on technology-based policy implementation.